2018
DOI: 10.18203/issn.2455-4529.intjresdermatol20180953
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study between intralesional PPD and vitamin D3 in treatment of viral warts

Abstract: <p class="abstract"><strong>Background:</strong> Viral warts are caused by human papillomavirus. There are innumerable treatment modalities but they may result in partial clearance or recurrence. Some newer and effective treatments include intralesional immunotherapy. We undertook a study to evaluate the safety and efficacy of two such immunotherapy namely tuberculin purified protein derivative (PPD) versus intralesional vitamin D3 for the treatment of viral warts.</p><p class="abstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
23
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 23 publications
(28 reference statements)
7
23
0
Order By: Relevance
“…There was an insignificant correlation between the number of lesions and the response to treatment. This is the same as reported by the recent study done by Singh et al 20 These findings may suggest that Vit.D 3 is highly effective regardless of the number of lesions. However, large‐scale studies are important to confirm these findings.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…There was an insignificant correlation between the number of lesions and the response to treatment. This is the same as reported by the recent study done by Singh et al 20 These findings may suggest that Vit.D 3 is highly effective regardless of the number of lesions. However, large‐scale studies are important to confirm these findings.…”
Section: Discussionsupporting
confidence: 92%
“…In our study, IL Vit.D 3 resulted in complete clearance of lesions in 70% of patients with plantar warts. In a recent study by Singh et al, 20 the response in Vit.D 3 group was complete cure in 29 patients (72.5%) which was similar to our study, while in PPD group, complete cure was reported in 32 patients (80%) which is higher than results of the current study that may be explained by increased number of sessions.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The response rate achieved was 78.57% with complete clearance in 82.60% of patients with palmoplantar warts. In addition, Singh, Mohan, Gupta, and Pandey () compared intralesional vitamin D3 with purified protein derivative (PPD) in various types of warts. Their results revealed that PPD was superior to vitamin D3 where 80% in the former group showed complete response versus 72.5% in the latter group but with no statistical significance.…”
Section: Discussionmentioning
confidence: 99%
“…Our results in this entity are closely matching to Abd El‐ sabour, Mohamed, and El Taiebb (2019) who found that in 62 patients injected with tuberculin PPD, 43 patients (69.4%) showed full cure and 13 (20.9%) patient showed weak response, six patients were lost from follow‐up. Singh, Mohan, Gupta, and Pandey (2018) compared between intralesional PPD and vitamin D3 in of viral warts treatment on 40 patients and he found that complete wart recovery occurred in 32 (80%) of patients, partial recovery occurred in 6 (15%) patients, and no response was found in two patients (5%). In the same direction, Saoji, Lade, Gadegone, and Bhat (2016) reported that out of 55 patients injected intralesionally by PPD, complete clearance was found in 42 (76%) of patients after four sessions while no efficacy was reported in 13 (24%) patients.…”
Section: Discussionmentioning
confidence: 99%